7
$\begingroup$

[Cross-posted here with no answers for a few days]

I came - to the very best of my knowledge from reading the source - across the following statement in The Jackknife and Bootstrap, Shao and Tu, p. 87:

$$\sum_i(X_i-\bar X)^4\leq16\sum_i(X_i-\mu)^4,$$

where $\bar X$ and $\mu$ are the sample mean and expected value of the $X_i$, respectively.

The statement appears in the broader context of their Theorem 3.8, which of course has several conditions. However, since the result seems to be algebraical, I suppose none of these matter for the present question.

Even without the term 16, the statement is well-known (for any $a$, not only $\mu$) when we replace 4 by 2.

My hunch is that the proof uses Pascal's triangle, as there are 16 terms in the r.h.s. when adding and subtracting $\mu$ and multiplying out:

$$\sum_i(X_i-\bar X)^4=\sum_i(X_i-\mu)^4+4(X_i-\mu)^3(\mu-\bar X)+4(X_i-\mu)(\mu-\bar X)^3+6(X_i-\mu)^2(\mu-\bar X)^2+(\mu-\bar X)^4$$

My attempts at bounding the terms on the r.h.s. (other than the first one, which is already in the "right" format), including Hölder's inequality, however have not led anywhere useful.

$\endgroup$
3
  • 1
    $\begingroup$ It would be sufficient to show $\sum(\bar X-\mu)^4\leq\sum(X_i-\mu)^4$, which certainly seems as though it should be true but doesn't seem all that easy to prove. $\endgroup$ Commented Jun 22, 2021 at 2:30
  • $\begingroup$ Indeed, that seems true, and amply so, as playing around with code like n <- 10; mu <- 4; x <- rnorm(n, mu); xbar <- mean(x); sum((xbar-mu)^4); sum((x-mu)^4) seems to suggest, so that one might expect the result to be easy to show - apparently, not. $\endgroup$ Commented Jun 22, 2021 at 6:35
  • 1
    $\begingroup$ I think the difficult case will be when $\mu$ is far from the data (which is unlikely but not impossible if it's really the mean) $\endgroup$ Commented Jun 22, 2021 at 22:10

2 Answers 2

3
$\begingroup$

So, I believe we have a proof - actually provided by my PhD Student Stephan Hetzenecker, who is however not here, so I'll post it in his name!

W.l.o.g., let $\mu = 0$ (otherwise define $Z_i := X_i - \mu$ and show $\sum_i(Z_i-\bar Z)^4 \leq 16 \sum_i Z_i^4 $). Using the binomial theorem, we obtain \begin{align} \tag{1}\label{eq:sum_binom} \sum_i(X_i-\bar X)^4= &\sum_i \left( X_i^4- 4X_i^3\bar X -4X_i\bar X^3 +6X_i^2\bar X^2 +{\bar X}^4\right). \end{align} Let $p \geq 1$. Using Jensen's inequality, we get \begin{align} \tag{2}\label{eq:applyJensen_p} \bar X^p := \left(\frac{1}{n} \sum_i X_i \right)^p \leq \frac{1}{n} \sum_i X_i^p. \end{align}

Hence, applying \eqref{eq:applyJensen_p} $n$ times for $p=4$, \begin{align} \tag{3}\label{eq:bound_barx4} \sum_i \bar X^4 = \sum_i \left(\frac{1}{n} \sum_j X_j \right)^4 \leq \sum_i \frac{1}{n} \sum_j X_j^4 = \sum_j X_j^4 . \end{align} Similarly, using Hölder's inequality with $p=q=2$ and using \eqref{eq:bound_barx4}, \begin{align} \tag{4}\label{eq:bound_barx2} \sum_i X_i^2 \bar X^2 &\leq \left(\sum_i X_i^4 \right)^{1/2} \left(\sum_i \bar X^4 \right)^{1/2}\\& \leq \left(\sum_i X_i^4 \right)^{1/2} \left( \sum_i X_i^4 \right)^{1/2} \\&= \sum_j X_j^4 . \end{align} Furthermore, using \eqref{eq:applyJensen_p} again \begin{align} \tag{5}\label{eq:bound_barx3} - \sum_i X_i\bar X^3 &= - n \bar X^4 \leq n \bar X^4 \\&\leq n \left(\frac{1}{n} \sum_j X_j^4 \right) \\&= \sum_j X_j^4 \end{align} Using Hölder's inequality with $p=4/3$ and $q=4$ and using \eqref{eq:bound_barx4}, \begin{align} \tag{6}\label{eq:bound_barx} -\sum_i X_i^3\bar X &\leq \sum_i \vert X_i^3\bar X \vert \\&\leq \left( \sum_i X_i^4 \right)^{3/4} \left( \sum_i \bar X^4 \right)^{1/4} \\&\leq \sum_i X_i^4 \end{align}

Combining \eqref{eq:sum_binom}, \eqref{eq:bound_barx4}, \eqref{eq:bound_barx2}, \eqref{eq:bound_barx3}, and \eqref{eq:bound_barx}, we obtain \begin{align*} \sum_i(X_i-\bar X)^4 \leq 16 \sum_i X_i^4, \end{align*} which was to be shown.

$\endgroup$
1
$\begingroup$

Let $A = 16\sum\limits_{i=1}^{n}(X_i-\mu)^4-\sum\limits_i(X_i-\bar X)^4$

$=\sum\limits_{i=1}^{n}\left(4(X_i-\mu)^2+(X_i-\bar X)^2\right)\left(2(X_i-\mu)+(X_i-\bar X)\right)\left(2(X_i-\mu)-(X_i-\bar X)\right)$

$=\sum\limits_{i=1}^{n}\left(4a_i^2+b_i^2\right)\left(2a_i+b_i\right)\left(2a_i-b_i\right)$, by letting $X_i-\mu=a_i$ and $X_i-\bar{X}=b_i$

Note that $\sum\limits_{i=1}^{n} b_i = \sum\limits_{i=1}^{n}X_i - n\bar{X}= n\bar{X}- n\bar{X} = 0$

Now, notice if $X_i$s are ordered in an increasing sequence, i.e., w.l.o.g. let $X_1\leq X_2\leq\ldots\leq X_n$, we shall have $a_1\leq a_2\leq\ldots \leq a_n$ and $b_1 \leq b_2 \leq \ldots b_n$, since $\mu, \bar{X}$ are constants.

$\implies 4a_1^2+b_1^2\leq4a_2^2+b_2^2\leq\ldots\leq 4a_n^2+b_n^2$ and $2a_1+b_1\leq 2a_2+b_2\leq\ldots 2a_n+b_n$

$\implies (4a_1^2+b_1^2)(2a_1+b_1)\leq(4a_2^2+b_2^2)(2a_2+b_2)\leq\ldots\leq (4a_n^2+b_n^2)(2a_n+b_n)$, since $4a_i^2+b_i^2 \geq 0$, being sum of squares of real numbers

Similarly, $2a_i-b_i=X_i-2\mu+\bar{X}$

$\implies 2a_1-b_1\leq 2a_2-b_2\leq\ldots\leq 2a_n-b_n$, since $X_1\leq X_2\ldots\leq X_n$

Now, let's use the following inequality from Chebyshev:

enter image description here

Now, applying Chebysev's inequality twice, we have,

$\frac{A}{n}=\frac{1}{n} \sum\limits_{i=1}^{n}\left(4a_i^2+b_i^2\right)\left(2a_i+b_i\right)\left(2a_i-b_i\right)\geq \left(\frac{1}{n} \sum\limits_{i=1}^{n}(4a_i^2+b_i^2)(2a_i+b_i)\right)\left(\frac{1}{n} \sum\limits_{i=1}^{n}(2a_i-b_i)\right)$

$\geq \left(\left(\frac{1}{n}\sum\limits_{i=1}^{n}(4a_i^2+b_i^2)\right)\left(\frac{1}{n} \sum\limits_{i=1}^{n}(2a_i+b_i)\right)\right)\left(\frac{1}{n} \sum\limits_{i=1}^{n}(2a_i-b_i)\right)$

$= \left(\frac{1}{n} \sum\limits_{i=1}^{n}(4a_i^2+b_i^2)\right)\left(\frac{1}{n} \sum\limits_{i=1}^{n}(2a_i)\right)\left(\frac{1}{n} \sum\limits_{i=1}^{n}(2a_i)\right)$, since $\sum\limits_{i=1}^{n}b_i=0$

$\geq \left(\frac{1}{n} \sum\limits_{i=1}^{n}(4a_i^2+b_i^2)\right)\left(\frac{1}{n} \sum\limits_{i=1}^{n}(2a_i)\right)^2 \geq 0$, being product of sum of squares of real numbers

$\implies A = 16\sum\limits_{i=1}^{n}(X_i-\mu)^4-\sum\limits_i(X_i-\bar X)^4\geq 0$

$\implies \sum\limits_i(X_i-\bar X)^4 \leq 16\sum\limits_{i=1}^{n}(X_i-\mu)^4$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.